Introduction to high performance computing for scientists and engineers - Hager, Georg; Wellein, Gerhard (Boca Raton [et al.] : CRC Press, 2011)
Designed for scientists, engineers, and students, this book presents a concise, practical introduction to high performance computing (HPC). It discusses the architecture of modern processors, providing a solid understanding of the performance potentials and limitations of current architectures and code. Moving from basic to advanced topics, the text covers key issues in HPC, including serial optimization, parallelism, OpenMP, MPI, and hybrid programming techniques. The authors also address advanced issues, such as solving affinity problems by pinning, writing efficient C++ code, and programmin
Includes bibliographical references and index
Chapter 11: Hybrid parallelization with MPI andOpenMPAppendix A: Topology and affinity in multicore environments; Appendix B: Solutions to the problems; Bibliography; Back cover;.
Online-Ausg.
Keywords: High performance computing; Science -- Data processing; Engineering -- Data processing; Hochleistungsrechnen; Naturwissenschaften; Ingenieurwissenschaften; Engineering / Data processing; High performance computing; Science / Data processing